Heuristic Strategies as Cognitive Bridges in Solving Arithmetic Sequence Word Problems: A Case Study - Fuad Rifai; M. Mahmudi Prasetiyo; Irbah Tsabitah (Universitas Sembilanbelas November Kolaka, 2026)
This study explores the micro-process dynamics of students in applying heuristic strategies to arithmetic sequence word problems through a qualitative case study. Using Think Aloud with the subject YD, the results show a paradox between procedural fluency with formulas and cognitive failure when switching to manual strategies. This transition triggers cognitive overload and representational misconceptions, where the subject is distracted by visuals, resulting in inconsistent answers. This study concludes that without a solid conceptual foundation, heuristic instruction risks weakening students' confidence and triggering logical errors, leading to a loss of focus in their work.